(untitled) (Journal of Medicine, 2025)
Introduction:The COVID-19 Pandemic has had a profound effect on the psychology of people around the world. It posed fear and anxiety to all, and pregnant women became more vulnerable. Various factors and the scarcity of treatment and hospital facilities during the lockdown worsened the mental state. Aim:The study was performed to assess pregnant women’s psychological impact and anxiety during the COVID-19 pandemic using a preset validated questionnaire. Methodology:This cross-sectional study was conducted among 553 pregnant women, who visited for antenatal care in the outpatient department of Obstetrics and Gynecology, Chittagong Medical College Hospital, and private chambers of researchers from October to December 2020. The psychological impact of the COVID-19 pandemic on pregnant women was assessed by the Italian version of the Impact of Event Scale (IES-R) questionnaire. A score of >24 was taken as significant. A six-item short-form of the Spielberger State-Trait Anxiety Inventory (STAI-6) scale was used to measure anxiety, and a score >36 was considered significant. Data were analyzed with SPSS-22 using the Chi-square test (for categorical data) and t-test (for numerical data) as appropriate. The NOVA test was done to calculate the significance between the groups. The P values <0.5 were taken as significant. Results: Among the participants(N-553), more than half (54%) of the participants had different grades (mild-27%, moderate-09%, and severe-18%) of psychological impact during the COVID-19 pandemic. The Mean (±SD) total IES-R score was 25.65(± 12.334) (range: 0-68); the STAI-6 score was above the cut-off value (i.e., > 36) [40.50 (± 15.027)] (range: 5-77). Severe IES-R scores were observed in women who attended private chambers than in government hospitals (p<0.001), and also in women among urban patients (p=0.001), middle-income group (p=0.001), and women who did not contact a doctor (p=0.001). Conclusion: The study revealed that more than half of the pregnant women experienced psychological impact during pregnancy. A subset of them might be vulnerable to PTSD. Almost all of the pregnant women in the study developed anxiety during COVID-19. Identifying protective factors targeted to eliminate the psychological impact and anxiety of pregnant women is warranted. J MEDICINE 2025; 26: 5-12